Racismo e Suas ‘sutilezas’: Uma Análise Integrada dos Impactos e Influências no Desenvolvimento Profissional e de Carreira de Pessoas Negras Brasileiras - Nunes, Juliana Pereira Rodrigues (2024)
For a long period, professional and career guidance did not place at the heart of the discussion the influence of contextual/structural aspects on people's career trajectories, especially the impacts of contexts on the careers of vulnerable groups, such as the Brazilian black population. . Given this scenario, this dissertation, through two studies, aimed to investigate the impacts and influences of racism and its nuances on the professional and career development of black Brazilian people. Article 1 investigated the influences of race/color on obtaining decent work and on the construction of professional trajectories of black workers. The results revealed that there is a perception that race/color is a career barrier and that factors such as education, income and social class mitigate difficulties. In addition to this, it was found that the conceptions of decent work, aligned with the ILO guidelines, do not always correspond to the reality perceived by the interviewees. Article 2 was the adaptation and presentation of the psychometric properties and invariance of the Racial and Ethnic Microaggressions Scale (REMS-45) for the black Brazilian population. The results indicated that the instrument has adequate psychometric properties and excellent reliability. Concomitantly, the evidence of external validity pointed to domains of racial microaggressions associated with income and education, reinforcing a solid base methodology for future investigations, as well as the promotion of practical welcoming actions, development of overcoming strategies and promotion of occupational and educational environments more inclusive. Thus, it is concluded that the contributions of the studies not only broaden the understanding of the challenges faced by black people in professional and career development, but also highlight the pressing need for more effective interventions within the scope of professional and career guidance, as well as of Organizational and Work Psychology. Therefore, it is expected that the work presented here will make a significant contribution to the advancement of knowledge and serve as a call to action to promote more equitable and inclusive environments in the Brazilian context.